COOPERATIVE EDUCATION: OPPORTUNITIES AND ADVANTAGES - Kaldibekova, Anargul Sotbarovna; M.Kh, Nishanova; Z.D, bralova; A.A., Sotbarov (International Journal of Psychosocial Rehabilitation, 2020)
The article highlights the need and opportunities for organizing cooperative education in the context of a credit-modular system. Based on the analysis of theoretical materials, the authors reveal the essence of the concepts of “cooperation”, “cooperative learning”, “cooperative education”. The article also describes the techniques, conditions for the formation of cooperative groups, as well as the nature and methods of applying the most widely used methods of cooperative education.